Dynamic changes in the uptake of dairy technologies in the Kenya Highlands - Baltenweck, Isabelle; Yamano, T.; Staal, Steven J. (Springer, 2011)
The purpose of this chapter is to investigate the dynamics in dairy production in the period following the liberalization using panel data on 874 agricultural households in the Kenya Highlands. Our estimation results indicate that the private milk marketing sector works effectively and thereby stimulates the adoption of improved dairy technologies. Similarly, we find that better market access facilitates the adoption of these technologies. In short, this chapter clearly demonstrates that improved marketing systems are a critical factor affecting the improvement of dairy production systems.